AI-Driven Security Posture Management: A Revolutionary Approach to Multi-Cloud Enterprise Security - Srinivas Reddy Cheruku (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The landscape of cloud security has undergone a transformative evolution, driven by the complexity of modern digital infrastructures and the escalating sophistication of cyber threats. This comprehensive article explores an innovative AI-driven Cloud Security Posture Management (CSPM) framework that transcends traditional security methodologies. By leveraging advanced machine learning algorithms, neural network architectures, and intelligent automation, the framework offers a proactive, adaptive approach to cybersecurity that addresses the multifaceted challenges of multi-cloud environments. The article demonstrates how intelligent systems can dynamically analyze network interactions, predict potential vulnerabilities, and implement rapid, context-aware response mechanisms, fundamentally reshaping how organizations conceptualize and implement security strategies.